2023
DOI: 10.1021/acs.analchem.2c04500
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic Surfactants can Modify the Thermal Stability of Globular and Membrane Proteins Interfering with the Thermal Proteome Profiling Principles to Identify Protein Targets

Abstract: The membrane proteins are essential targets for understanding cellular function. The unbiased identification of membrane protein targets is still the bottleneck for a system-level understanding of cellular response to stimuli or perturbations. It has been suggested to enrich the soluble proteome with membrane proteins by introducing nonionic surfactants in the solubilization solution. This strategy aimed to simultaneously identify the globular and membrane protein targets by thermal proteome profiling principl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The introduction of non-ionic detergent NP40 to TPP has been demonstrated to be able to alter protein thermal stability in previous studies [ 18 , 21 ]. However, there is no definitive conclusion on whether the introduction of detergents impacts the target identification performance of TPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of non-ionic detergent NP40 to TPP has been demonstrated to be able to alter protein thermal stability in previous studies [ 18 , 21 ]. However, there is no definitive conclusion on whether the introduction of detergents impacts the target identification performance of TPP.…”
Section: Discussionmentioning
confidence: 99%
“…Reassuringly, the number of identified kinase targets was remarkably improved, and was comparable to that identified without detergents at 52 °C. A very recent study [ 21 ] also reported that the non-ionic detergent NP40 can modify protein thermal stability, and they therefore concluded that the introduction of detergents may not be compatible with the principles of TPP for target identification. Different from that conclusion, our results underscore the importance of using a lower temperature range in TPP for efficient target identification when utilizing detergents (either non-ionic or zwitterionic).…”
Section: Introductionmentioning
confidence: 99%
“…Although this increases proteomic coverage (>8000 protein groups), recent research shows data indicating their destabilizing effects on the proteome. The average melting temperature across the proteome decreases upon the addition of detergent, leading to increased protein precipitation (Refs 48 , 49 ).…”
Section: Target Deconvolution Based On Thermal Denaturationmentioning
confidence: 99%
“…In a recent publication by Kalxdorf et al, selective enrichment of glycosylated cell surface proteins was combined with CETSA MS to effectively identify compound binding to extracellular membrane receptors. Another approach is the use of detergents to solubilize the membrane-bound proteins and thereby increase the number of membrane proteins detected. , However, the use of a detergent remains challenging and interferes with the protein stability after the heat step . One successful example of the use of detergent in CETSA MS to identify membrane protein targets was reported by Carnero Corrales et al In this target deconvolution study of the autophagy inhibitor indophagolin, the purinergic receptor P2X4 was identified as a protein target in cell lysate with detergent.…”
mentioning
confidence: 99%
“…3,27 However, the use of a detergent remains challenging and interferes with the protein stability after the heat step. 27 One successful example of the use of detergent in CETSA MS to identify membrane protein targets was reported by Carnero Corrales et al 28 In this target deconvolution study of the autophagy inhibitor indophagolin, the purinergic receptor P2X4 was identified as a protein target in cell lysate with detergent. This was confirmed by Western blot-based CETSA.…”
mentioning
confidence: 99%